Fear and Reward Circuit Alterations in Pediatric CRPS - Simons, Laura E.; Erpelding, Nathalie; Hernandez, Jessica M.; Serrano, Paul; Zhang, Kunyu; Lebel, Alyssa A.; Sethna, Navil F.; Berde, Charles B.; Prabhu, Sanjay P.; Becerra, Lino; Borsook, David (Frontiers in Human Neuroscience, 2016)
In chronic pain, a number of brain regions involved in emotion (e.g., amygdala, hippocampus, nucleus accumbens, insula, anterior cingulate, and prefrontal cortex) show significant functional and morphometric changes. One phenotypic manifestation of these changes is pain-related fear (PRF). PRF is associated with profoundly altered behavioral adaptations to chronic pain. For example, patients with a neuropathic pain condition known as complex regional pain syndrome (CRPS) often avoid use of and may even neglect the affected body area(s), thus maintaining and likely enhancing PRF. These changes form part of an overall maladaptation to chronic pain. To examine fear-related brain circuit alterations in humans, 20 pediatric patients with CRPS and 20 sex- and age-matched healthy controls underwent functional magnetic resonance imaging (fMRI) in response to a well-established fearful faces paradigm. Despite no significant differences on self-reported emotional valence and arousal between the two groups, CRPS patients displayed a diminished response to fearful faces in regions associated with emotional processing compared to healthy controls. Additionally, increased PRF levels were associated with decreased activity in a number of brain regions including the right amygdala, insula, putamen, and caudate. Blunted activation in patients suggests that (a) individuals with chronic pain may have deficits in cognitive-affective brain circuits that may represent an underlying vulnerability or consequence to the chronic pain state; and (b) fear of pain may contribute and/or maintain these brain alterations. Our results shed new light on altered affective circuits in patients with chronic pain and identify PRF as a potentially important treatment target.